ETIOLOGY OF PERIODONTAL DISEASE – MICROBIOLOGY AND BIOFILM - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira; Santos, Carolina Carvalho de Oliveira (Seven Editora, 2026)
The etiology of periodontal disease is directly related to dental biofilm, an organized microbial community that, when unbalanced, triggers inflammatory processes responsible for the destruction of dental support tissues. Understanding the disease has evolved from theories focused solely on the amount of bacterial plaque to ecological models that emphasize microbial dysbiosis, the interaction between key pathogens, and the host response. Furthermore, local, systemic, and environmental factors influence the formation, maturation, and pathogenicity of biofilm, making its control essential for the prevention and treatment of periodontal diseases.